Needle stick injury and associated factors among acupuncture practitioners: a cross-sectional study in China - Jiang, Wenjing; Liu, Ying; Cao, Li; Zhou, Ping; Dai, Anna; Tang, Juan (Frontiers in Public Health, 2024)
BackgroundNeedle stick injury (NSI) is one of the most common and severe occupational hazards for healthcare workers (HCWs), leading to both physical harm and psychological distress and ultimately affecting patient safety. Previous studies on NSI were predominantly focused on general clinical practice, and limited research has targeted specifical NSI occurring in acupuncture practice in China, which has the greatest use of acupuncture.ObjectiveThis study aimed to investigate NSI and associated factors among acupuncture practitioners in China.MethodsA cross-sectional online survey was conducted among acupuncture practitioners across 98 hospitals in southwest China from April to May 2024. A researcher-developed questionnaire was used to collect participants’ experiences of NSI, general information, and knowledge, behavior, and risk perception related to occupational exposure. Multivariate logistic regression was employed to examine factors associated with NSI.ResultsA total of 578 acupuncture practitioners completed the questionnaire, among whom 34.3% experienced at least one NSI in the past three years, yet 46.0% of these incidents were not reported. Factors associated with an increased risk of NSIs included postgraduate education or higher (OR = 2.174, 95% CI: 1.020, 4.634), high probability of occupational exposure (OR = 2.940, 95% CI: 1.826, 4.735), moderate perception of exposure severity (OR = 9.149, 95% CI: 1.948, 42.97), and high perception of exposure severity (OR = 7.025, 95% CI: 1.497, 32.969). Conversely, factors associated with a reduced risk of NSIs included females (OR = OR = 0.576, 95% CI: 0.379, 0.876), nurses (OR = 0.396, 95% CI: 0.210, 0.746), working in other professions (OR = 0.362, 95% CI: 0.151, 0.868), adherence to standard preventive measures (OR = 0.396, 95% CI: 0.210, 0.746), and consistent adherence to post-exposure procedures (OR = 0.092, 95% CI: 0.021, 0.398).ConclusionNSI is common among acupuncture practitioners in Chinese medical institutions, and under-reporting is significant. Our findings suggest that standard prevention strategies, adherence to exposure protocols, enhanced training, and effective reporting policies may help reduce NSI and improve reporting rates.